Kewenangan Badan Pemeriksa Keuangan dan Pembangunan (BPKP) Melakukan Audit Investigasi Guna Menentukan Kerugian Keuangan Negara - Sukamto Satoto; Fitria Fitria (Universitas Batanghari Jambi, 2022)
The purpose of this study is to identify and understand and analyze in depth the authority of the Financial and Development Supervisory Agency in conducting investigative audits. The problems raised in this study discuss the authority of the Financial and Development Supervisory Agency in conducting investigative audits and what are the Implications of the Financial and Development Supervisory Agency's Investigation Audit on State Financial Losses in Law Enforcement. This study uses a normative method with the steps of description, systematization and explanation of the contents of positive law in depth using a concept approach, a law approach and a case approach using a systematic synchronization analysis. The results showed that the feedback from the investigative audit enabled the realization of financial management and supervision reforms including the integration between activity planning and budgeting. Thus, fiscal transparency and accountability are very urgent in reforming the management and supervision of state finances, because transparency and accountability in managing state finances can reduce state losses. As the government's internal auditor, the Financial and Development Supervisory Agency is authorized to supervise finance and development. On the other hand, the Financial and Development Supervisory Agency has the authority to conduct investigative audits to determine whether or not there has been a loss in state finances at the request of law enforcement. The implications of the investigative audit carried out by the Financial and Development Supervisory Agency in addition to imposing an obligation on financial managers to return state financial losses based on the results of the investigative audit, the results of the investigative audit also have consequences in the law enforcement process, because the results of the investigative audit are in the form of documents and information provided by auditors in court can affect the judge's confidence in the examination of the trial in court.